Split Ticket Voting: Menumbuhkan Kegairahan Politik Lokal? - Ratri Istania (Puslatbang KDOD Lembaga Administrasi Negara, 2009)
The Constitutional Court decisions upon majority vote in the election for legislative candidate replaces the traditional ballot system. Many political observers predict the application of majority vote might cause an increase of split-ticket voting in the 2009 election, especially for house of representative election. Though, split ticket voting is not unique to Indonesian election case, it seems to be a good alternative to create more vibrant local politics. Moreover, Paramadina University Rector, Anies Baswedan (2008), said, “split ticket voting will also enhance the development of local democracy [in which] a voter can choose their legislative candidate from different political party affiliation for each government level. [For example], a voter can choose the candidate from A political party for national legislative body (DPR). A candidate from B political party is choosen for provincial level legislative body (DPRD provinsi). And a candidate from C political party is for kabupaten legislative body (DPRD kabupaten).” However, this positive image of split- ticket voting has not been accompanied by sufficient analysis on its impact to local politics. This paper seeks to address the question on the impact of split ticket voting in creating more vibrant local politics. How split-ticket voting influences the Indonesian political party and election reform agenda? What split ticket voting can do for the local politics? And the last question is how split ticket voting relates to the planning of electoral district boundaries (daerah pemilihan), and redistricting, such as pemekaran, in the local regions. To answer them, I review the literature and related government policy which will be divided into three parts: first, analyzing theoretical background and concepts of split- ticket voting; second, pros and cons of split-ticket voting in Indonesia local politics; third, studying the electoral system reformation: the inconsistency between electoral district planning and pemekaran policies; fourth, analyzing the future possibility transformation from “pemekaran” to redistricting policy: as a recommendation; and finally, conclusion. Keywords: Split-ticket Voting, Partai Politik, Calon Legislatif, Pemilih, Politik Lokal, Daerah pemilihan, Pemekaran, Redistricting.